Application of Remote Follow-Up Via the WeChat Platform for Patients who Underwent Congenital Cardiac Surgery During the COVID-19 Epidemic - Zhang,Qi-Liang (2021)
Abstract Objective: To investigate the effect of WeChat-based telehealth services on the postoperative follow-up of children who underwent congenital heart surgery during the COVID-19 epidemic. Methods: This study retrospectively analyzed the clinical and family data of 108 children who underwent congenital heart surgery and underwent remote follow-up via the WeChat platform from December 2019 to March 2020 in our hospital. Results: During the follow-up period, the WeChat platform was used to refer 8 children with respiratory infection symptoms to local hospitals for treatment. Two children with poor incision healing were healed after we used the WeChat platform to guide the parents in dressing the wounds on a regular basis at home. Nutritional guidance was given via the WeChat platform to 13 patients with poor growth and development. The psychological evaluation results of the parents showed that the median (range) SDS score was 43 (34-59), and 7 parents (6.5%) were classified as depressed; the median (range) SAS score was 41 (32-58), and 12 parents (11.1%) were classified as having mild anxiety. Conclusion: The use of WeChat-based telehealth services was effective for the remote postoperative follow-up of children who underwent congenital cardiac surgery during the COVID-19 epidemic. Providing WeChat-based telehealth services can reduce the amount of travel required for these children and their families, which is helpful for controlling and preventing the spread of COVID-19.